Pengaruh Inflasi, Suku Bunga, dan Nilai Tukar terhadap Nilai Perusahaan pada Perusahaan Subsektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2017–2022 - Murjiani, Dini; Reza Adiyanto, Mochamad (JURNAL AKUNTANSI DAN MANAJEMEN, 2023)
Economic fluctuations in a country can influence firm value, particularly in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX). This study aims to examine the effect of inflation, interest rates, and exchange rates on firm value, both simultaneously and partially. A quantitative research method was employed using multiple linear regression analysis. The results of the F-test indicate that inflation, interest rates, and exchange rates collectively have a positive and significant impact on firm value. However, the t-test results show that inflation has a negative and insignificant effect on firm value, interest rates have a positive and significant effect, while exchange rates have a negative and insignificant effect. These findings suggest that among the examined macroeconomic variables, interest rates play the most influential role in determining firm value within the food and beverage sub-sector listed on the IDX.